Cephalometric comparison of obstructive sleep apnea patients and healthy controls - Gungor, Ahmet Yalcin; Turkkahraman, Hakan; Yilmaz, H. Huseyin; Yariktas, Murat (European Journal of Dentistry, 2013)
Objective: This parallel controlled clinical trial evaluated the effect of a gel containing Lippia sidoides essential oil on plaque and gingivitis control.Methods: Thirty patients (n=30) were randomly selected and allocated into three groups: Lippia sidoides (LS, n=10), chlorhexidine (CLX, n=10) or placebo (control, n=10). Plaque and bleeding index were recorded at baseline and after three months. All volunteers were instructed to brush with the gel three times a day throughout the experiment period.Results: There was a significant reduction on plaque and gingivitis in the test groups (P<.05), but no statistically significant difference was observed between them (P<.05).Conclusion: A gel preparation containing 10% Lippia sidoides essential oil was an efficient herbal antiplaque and antigingivitis agent. (Eur J Dent 2013;7:28-34)
Keywords: Oral hygiene; gingival status; dental students